Large magneto-thermopower in MnGe with topological spin texture - Y. Fujishiro (Nature Portfolio, 2018)
Topological spin textures produce versatile electronic functionalities, but are scarcely exploited for achieving heat to electricity conversion. Here, Fujishiro et al. attribute an enhanced magneto-thermopower in MnGe with topological spin hedgehogs, to electron scattering via the dynamics of an emergent magnetic field.